2008
DOI: 10.3389/neuro.11.005.2008
|View full text |Cite
|
Sign up to set email alerts
|

Brian: a simulator for spiking neural networks in Python

Abstract: “Brian” is a new simulator for spiking neural networks, written in Python (http://brian. di.ens.fr). It is an intuitive and highly flexible tool for rapidly developing new models, especially networks of single-compartment neurons. In addition to using standard types of neuron models, users can define models by writing arbitrary differential equations in ordinary mathematical notation. Python scientific libraries can also be used for defining models and analysing data. Vectorisation techniques allow efficient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
208
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(219 citation statements)
references
References 13 publications
(16 reference statements)
2
208
0
Order By: Relevance
“…In particular we implemented the same network in Neuron (Carnevale and Hines, 2006), NEST (Gewaltig and Diesmann, 2007), Brian (Goodman and Brette, 2008) and our own simulator Auryn (Methods). The network was tuned initially to a parameter regime in which the model exhibits stable asynchronous irregular activity over extended periods of time (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…In particular we implemented the same network in Neuron (Carnevale and Hines, 2006), NEST (Gewaltig and Diesmann, 2007), Brian (Goodman and Brette, 2008) and our own simulator Auryn (Methods). The network was tuned initially to a parameter regime in which the model exhibits stable asynchronous irregular activity over extended periods of time (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…RNN learning is used for context-sensitive languages recognition and is a difficult and often increasing problem for standard recurrent neural networks (RNNs), because it requires unlimited memory resources. Authors (Goodman, Brette 2008;Schmidhuber et al 2005;Schmidhuber et al 2006) found that Evolino based LSTM learns on average faster and it is able to generalize substantially better that gradient-based LSTM. It is possible using Evolino to learn functions composed of multiple superimposed oscillators such as double sine and triple sine.…”
Section: Description Of Evolino Neural Networkmentioning
confidence: 94%
“…The Brian simulator (Goodman and Brette 2008) has become very popular among neuroscientists in just a few years and it has been ranked 2nd most popular neural simulator in a recent survey (Hanke and Halchenko 2011), just after the well known Neuron software (Carnevale and Hines 2006). The reason behind this success is certainly the intuitive and highly flexible interface offered by Brian as well as efficient vectorized computations that make Brian quite competitive with regular C code for large networks.…”
Section: Brian Limitationsmentioning
confidence: 97%